Veranicos no estado do Tocantins e a cultura da soja - Roldão, Aline de Freitas (2020)
In the state of Tocantins, the semi-humid tropical climate predominates with alternation of two seasons, one rainy and the other dry. The rainfall totals during the rainy season are favorable to the development of temporary crops such as soybeans. However, the great concern of farmers is not limited to the total rainfall, but to the way in which rainfall distribution often occurs, that is, due to the occurrences of droughts in the rainy season, which we call dry spell. Therefore, this research has as main objective to propose and apply criteria and methods of recognition and classification of dry spells, the spatialization of the phenomenon and the analysis of the probability of its occurrence in the state of Tocantins. Besides that, this research verifies the consequences arising from them in Tocantins, in relation to soybean culture, including an assessment of the relationship of the phenomenon to the occurrence of El Niño. The methodology of this research started with the collection of rainfall data from 56 seasons within the study area and 27 in its surroundings, according to the National Water Agency, from 1985 to 2016. Data related to soybeans were analysed from the IBGE Automatic Recovery System, through the item “municipal agricultural production”, covering the period from 1988 to 2016. The calculation of the water balance was done to obtain the values of the potential evapotranspiration, which is fundamental in determining the rainy season and also in the recognition of dry spells. After identification, the dry spells were divided into 4 classes of duration: class A (6 to 10 days); class B (11 to 15 days); class C (16 to 20 days) and class D (> 20 days). The phenomenon was spatialized in Tocantins' territory using the QGIS 2.18.28 software and the interpolator was Multilevel b-spline interpolation. The probability of occurrence of dry spells was calculated using the ratio / fraction of probability. In order to analyze the relationship between dry spells and soybean yield and between dry spells and El Niño, were used the statistical tests: Chi-Square (X²) Pearson's and Fisher's Test. From the methodological procedures carried out, the results found were diverse, among which the most relevant are: the rainy season in Tocantins begins in November and ends in April, which is also a period of water surplus in the soil. During the analyzed period, 8,608 events of the meteorological phenomenon were recorded in pluviometric stations, in Tocantins. Class A (6 to 10 days) was the most frequent, with 76% of the episodes recorded, then class B (11 to 15 days) with 17% of events, class C (16 to 20 days) represents 5% of the total found and finally class D (> 20 days) with only 2%. The dry spells do not occur uniformly in Tocantins and the southeastern portion of the state, especially the micro region of Dianópolis is the one that has the greatest representativeness of the phenomenon. On the other hand, the central-western portion of the state, includes the areas with the lowest occurrences of dry spells, especially the microregions of Miracema do Tocantins and Formoso River. Class A (6 to 10 days) is the most likely to occur, while Class D (> 20 days) is the least likely to occur in the state. Regarding the relationship between the occurrence of dry spell and soybean productivity, it was found that the occurrence of dry spell of class B (11 to 15 days) in November and, class C (16 to 20 days) in January, decreased the productivity of oilseed. Finally, it is worth noting that this research is mainly aimed at guiding actions related to the state's agricultural production, providing support to Tocantins' farmers, especially those who grow soybeans.